Whole‐tumor histogram analysis of monoexponential and advanced diffusion‐weighted imaging for sinonasal malignant tumors: Correlations with histopathologic features. Issue 1 (4th July 2019) - Xiao, Zebin; Tang, Zuohua; Zhang, Jing; Yang, Guang; Zeng, Wenjiao; Luo, Jianfeng; Song, Yang; Zhang, Zhongshuai
Abstract : Background: The histopathological basis of monoexponential diffusion‐weighted imaging (DWI), intravoxel incoherent motion (IVIM), and diffusion kurtosis imaging (DKI) in the characterization of sinonasal malignant tumors is still unclear. Purpose: To explore the correlations of histogram metrics from monoexponential DWI, IVIM, and DKI with histopathologic features in sinonasal malignant tumors. Study Type: Retrospective. Subjects: In all, 76 patients with sinonasal malignant tumors. Field Strength/Sequence: Fourteen different b values ( b = 0, 50, 100, 150, 200, 250, 300, 350, 400, 800, 1000, 1500, 2000, and 2500 sec/mm 2 ) were used to perform different DWI models at 3.0T. Assessment: The whole‐tumor histogram metrics were calculated on the apparent diffusion coefficient (ADC), pure diffusion coefficient ( D ), pseudodiffusion coefficient ( D* ), perfusion fraction ( f ), diffusion kurtosis (K), and diffusion coefficient (Dk) maps. Histopathologic features, including nuclear, cytoplasmic, cellular, stromal fractions, and the nuclear‐to‐cytoplasmic (N/C) ratio, were measured. Statistical Tests: Spearman correlations and stepwise multiple linear regression analyses were performed to determine the correlations between histogram metrics and histopathologic features. Results: ADC, Dk, and f histogram metrics showed significant correlations with investigated histopathologic features; D and K histogram metrics were significantly correlated with cellular, stromal, and nuclear fractions (all P < 0.05). Significant correlations between the 75th percentile of D and cytoplasmic fraction and between the kurtosis of K and the N/C ratio were observed ( P < 0.05). The skewness of Dk, K, and the 75th percentile of D were independently associated with cellular and nuclear fractions; the skewness of Dk and K were independently associated with stromal fraction ( P < 0.05). Data Conclusion: Monoexponential and advanced DWI histogram parameters were significantly correlated with histopathologic features in sinonasal malignancies. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;51:273–285.